Epilepsy Surgery Quality of Life and Seizure Control Outcomes - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 2010)
A consecutive, retrospective analysis of seizure control and quality of life was performed in 83 patients who underwent epilepsy surgery at Children's Hospital of Wisconsin, Milwaukee, WI.